The Influence of Tax Avoidance and Earnings Management on Cost of Equity Capital: The Moderating Role of Managerial Ownership - Elisa; Syahdan, Saifhul Anuar; Ruwanti, Gemi; Koroy, Tri Ramaraya (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study aims to analyze the effect of tax avoidance and earnings management on the cost of equity capital, with managerial ownership as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The research adopts a quantitative approach using secondary data derived from audited annual financial statements. The sampling technique employed is purposive sampling based on specific criteria, resulting in a total of 55 companies that met the data completeness requirements. The variables in this study include tax avoidance (measured by the Effective Tax Rate), earnings management (measured using the Modified Jones Model 1995), cost of equity capital (measured using the Capital Asset Pricing Model), and managerial ownership (measured by the proportion of managerial shareholding). The data were analyzed using the Moderated Regression Analysis (MRA) technique with the assistance of SPSS software. The findings indicate that tax avoidance positively affects the cost of equity capital. Meanwhile, earnings management has a negative effect on equity capital costs. Managerial ownership moderates the relationship between both tax avoidance and earnings management on the cost of equity capital.